KETERCAPAIAN PROGRAM SLQ DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN MAHASISWA PAI UNIVERSITAS MUHAMMADIYAH MALANG - Ianatut Thoifah; Zulfikar Yusuf; Saeful Biantoro (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This study aims to determine the achievement of the SLQ program in improving the ability to read Qur’an students of the Islamic Religious Education Program, University Muhammadiyah of Malang. This study uses a descriptive qualitative approach with data analysis of Miles, Huberman and Saldana, namely data condensation where the data is adjusted to the needs and simplified by a percentage to make it easier to read the results, then display and conclusions / verification. The results of this study indicate the achievement of the SLQ program in improving reading Qur’an students of Islamic Religious Education Program consists of five components with a very varied increase, the highest score is dominated by a percentage of 31% PAI students are able to read al Qur'an with makharijul huruf, tajwid and sifatul huruf, in addition to the overall percentage SLQ achievement in improving the Qur’an reading skills of students PAI is 88.28% from100%, then 11.72% are students of PAI did not experience increase in ability from the first abilities possessed during the SLQ activities.